Studying the Effect of Addition Particles of Alumina (Al2O3) and Zirconia (ZrO2), on Some Mechanical Properties for Matrix Composites (Al-Si-Mg) Alloy - I. Ibrahim, Sarmad (Al-Khwarizmi Engineering Journal, 2011)
This study is concerned with the effect of adding two kinds of ceramic materials on the mechanical properties of (Al-7%Si- 0.3%Mg) alloy, which are zirconia with particle size (20μm > P.S ≥ 0.1μm) and alumina with particle size (20μm > P.S ≥ 0.1μm) and adding them to the alloy with weight ratios (0.2, 0.4, 0.6, 0.8 and 1%). Stirring casting method has been used to make composite material by using vortex technique which is used to pull the particles to inside the melted metals and distributed them homogenously. After that solution treatment was done to the samples at (520ºC) and artificial ageing at (170ºC) in different times, it has been noticed that the values of hardness is increased with the aging time of the original alloy and reached its highest value after (8hr). Mechanical tests were done to the original alloy and the composite material at the maximum hardness value and represented by tensile, hardness, and wear tests. It was found that the hardness value is increased with increment of the amount of added particles; also the increment in the hardness of the alloy which is reinforced with alumina is more than that reinforced with zirconia. Regarding the tensile test, results show that the strength and yield resistance of the composite material are more than that in the original alloy and these values are increased with increasing the amount of the added particles and they reached maximum values at (0.6%). Then they are decreased but these values remain at higher values than those in the original alloy. However, the ductility is decreased as compared with the original alloy and this decrement was more obvious with the increasing amount of the added particles. The increment of strength and yield resistance of the alloy reinforced by alumina was higher than that reinforced with zirconia, while the ductility of the alloy reinforced by zirconia was higher than that happened by the addition of alumina. Also zirconia and alumina addition to the original alloy decreased the wear rate, and the decrement would be more with the increased amount of adding particles. In addition the wear resistance of the alloy reinforced with alumina was larger than that reinforced with zirconia. X-rays testing proved that secondary phase (AlFeSi) appeared in both original alloy and the composite material. While heat treatment led to the appearance of phases (Mg2Al) and (Mg2Si) in original alloy. This was led to obvious improvement in the mechanical properties in addition to appearance ceramic particles in the microstructure of the composite material. This structure somewhat homogenous has fine grains as compared with large grains in the microstructure of the original alloy. .